(untitled) (European Journal of Multidisciplinary Studies, 2023)
Philosophy in its traditional sense is regarded as a discipline that focuses on thought, reason and ideas. It is indifferent to action, where psychology, sociology and anthropology have taken this role. The pragmatists concern is the gap between thought and action. Returning the attention to action led to pragmatism being seen and valued more as a moral philosophy and behavioral psychology. This is precisely where the interest of this philosophy lies; how people can improve themselves and the world, expressed with the concept of 'meliorism'. Before that, James, Piers, etc. enter the philosophical discourse, revealing the principles and methodology of the study itself, the meaning and explanation of phenomena. Hence, the connection between gnosiology and morality is essential. The issue becomes even more complex, because from the discovery of the truth it moves to human identity, culture and the need for progress. The concreteness of this optimistic philosophy is achieved through education. Meanwhile, the discourse will arise between the questions: What is the truth for pragmatists? How is the relationship between truth, individual and society expressed phenomenologically? How can it be passed without harsh frustrations towards progress?